THE MEDIATING EFFECTS OF QUALITY OF WORK LIFE ON CAPACITY PERFORMANCE MANAGEMENT AND EMOTIONAL INTELLIGENCE - Hermawati, Adya; Husin, Husin; Sitorus, Sunday Ade; Djajanto, Ludfi; Bahri, Syamsul; SUNDAY ADE SITORUS (Universitas Brawijaya, Indonesia, 2021)
This study evaluated the impact of leadership management skills and emotional intelligence on employee performance as a variable mediation through the quality of work life. This research uses a path analysis model (path analysis) since there is a mediation between the independent variables and the dependent variable to analyze the mediating impact of the quality of work-life on managerial leadership and emotional intelligence on employee efficiency. This analysis is called a universal survey (free sampling) or census using all population members, which amounts to 33 people. Management capacity led significantly to performance. Employee emotional intelligence also provides a valuable contribution to success. The standard of work has made a significant difference in the results. The managerial capability of the chief has made a positive contribution to the efficiency of the job. Employee emotional intelligence is also a positive contribution to job performance. K Quality in management, accompanied by the quality of work, has been a successful contribution to performance. Employee emotional intelligence was a positive contribution to results, followed by job efficiency. The study will contribute positively to the understanding of the job evaluation of BNN employees in Malang City. However, this analysis contributes to the assessment of BNN employees based on the job evaluation of BNN employees in Malang City. The difference between this study and previous studies is the treatment or care of Malang City BNN employees to improve the quality of their assessment.